The Bad Secret : Poems - Harris, Judith, 1955- (Book collections on Project MUSE., 2006)
The Bad Secret takes readers on a dark yet sometimes comic sojourn through the undercurrents of a life suddenly unmoored by grief, and then to the subsequent rise of the spirit to recovery. Tough-minded and intellectual, Judith Harris's poems are also distinguished by brilliant images close to metaphysical. They reflect on childhood, nature, mental and physical illness, the loss of a mother, and the levity of being simply human. In a voice entirely her own, Harris confronts life's secrets with their hidden meanings inspired by guilt and redemption, offering a music of tenderness and hope. I watch it gutter down, over the pine's edge, over the pink and orange sunset, diving into the abyss, with its wings perpendicular to the ravine. By now, I have broken offfrom the rest, pretending I'm an orphan -- my eyes fixed on the unseeable destruction of my ghost in that suicidal machine. "Hush," I say, as if hatred was a sound, as if I could make the negative positive, but nature itself has given up on the picture of my happy family, and pretends not to look at the box with the rolled-up Kodak filmtumbling over the ledgegathering more weight and velocity. -- "My Father Throws His Camera Down the Grand Canyon, 1968."